Participatory, Multimodal Approaches to Child Rights Education in Global Contexts: Reflections on a Study with Schoolchildren in Uganda and Canada - Jones, Shelley; Manion, Kathleen (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2023)
Although a child’s prerogative to know their rights is enshrined in the United Nations Convention on the Rights of the Child and other documents such as the African Charter on Rights and Welfare of the Child, child rights are rarely introduced to children as part of their formal learning experience in school. Children are deemed unable to understand the concepts of rights and responsibilities (Alderson, 2008; Jerome, 2018) and educators do not know how to integrate them into their teaching. This lack of child rights education means children do not possess the awareness and knowledge needed to claim and exercise their rights (Covell et al., 2017; Wabwile, 2016). Drawing on a case study conducted in Uganda and Canada, this paper explores ways that participatory, empowering, multimodal, and contextually responsive approaches to child rights education enables children and their teachers to meaningfully explore and learn about children’s rights.